2016
DOI: 10.1007/s00709-016-0959-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen treatment enhances sterols and withaferin A through transcriptional activation of jasmonate pathway, WRKY transcription factors, and biosynthesis genes in Withania somnifera (L.) Dunal

Abstract: The medicinal plant Withania somnifera is researched extensively to increase the quantity of withanolides and specifically withaferin A, which finds implications in many pharmacological activities. Due to insufficient knowledge on biosynthesis and unacceptability of transgenic approach, it is preferred to follow alternative physiological methods to increase the yield of withanolides. Prior use of elicitors like salicylic acid, methyl jasmonate, fungal extracts, and even mechanical wounding have shown to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Selected endophyte inoculation could increase the in planta content of IAA in leaves and roots that could enhance withanolide biosynthesis. Improvement of withaferin A production by application of nitrogen significantly upregulating structural and regulatory genes of withanolide biosynthesis also supports our present observation 50 . The previous report demonstrated that IAA favours the biosynthesis of withaferin A in in-vitro root cultures of W. somnifera 51 consolidates the role of IAA producing endophytes in enhancing the content of withaferin A in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Selected endophyte inoculation could increase the in planta content of IAA in leaves and roots that could enhance withanolide biosynthesis. Improvement of withaferin A production by application of nitrogen significantly upregulating structural and regulatory genes of withanolide biosynthesis also supports our present observation 50 . The previous report demonstrated that IAA favours the biosynthesis of withaferin A in in-vitro root cultures of W. somnifera 51 consolidates the role of IAA producing endophytes in enhancing the content of withaferin A in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In our previous study, nitrogen treatment enhanced the accumulation of phytosterols and withanolides, which were correlated with induced expression of WsWRKY1 (expressed sequence tag (EST) accession number ), indicating the possible role of WsWRKY1 in the regulation of triterpenoids (Pal et al ., ). Here, to further investigate the involvement of WsWRKY1 in the regulation of triterpenoid withanolide biosynthesis, its expression was evaluated in response to MeJA and salicin that are known to induce withanolides accumulation in W. somnifera (Rana et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In this study, we set out to investigate the transcriptional regulation of triterpenoid withanolide biosynthesis in W. somnifera . Our previous study found that a particular TF belonging to the WRKY class ( WsWRKY1 ) was highly induced in response to nitrogen treatment, with a corresponding increase in withanolides (withaferin A) as well as phytosterols (Pal et al ., ). Here, a series of investigations was carried out to further determine the functional role of WsWRKY1 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The expression profiles of these CYPs showed chemotype-specific and tissue-specific variation, as well as variation in response to physiological and developmental factors. To expand the understanding of expression of genes in relation to withanolide biosynthetic pathway, Pal et al ( 2016 ) perform experiments with different concentrations of fertilizers on fresh twigs of W. somnifera . Treated twigs related to highest accumulation of withaferin-A has been selected to analyse expression pattern of CYPs, allene oxide cyclases (AOCs) and few other pathway related genes.…”
Section: Proposed Pathways For Biosynthesis Of Withanolides: Medicinamentioning
confidence: 99%